Perbandingan Aplikasi Redo Dan Acronis Sebagai Cloning Harddisk Menggunakan Jaringan Komputer - Nina Kurniawati; Guntara Hafri Wiyatno; Saguh Widiastoko; Ahmad Agus Surury (LPPM STIKI MALANG, 2022)
Cloning is the process by which the contents of a harddisk move to another harddisk. This process can make it easier for users not to install the the operating system and install applications from scratch. Harddisk cloning over the network is done by moving the master harddisk (harddisk source) to the slave harddisk (Harddisk destinaton). In the process of cloning with a network, the main harddisk and the second harddisk to be cloned remain on their respective computers without moving the second harddisk to the main harddisk to be parallel. There are many application programs used in the hard disk cloning process over the network, among which will e discussed, namely Redo Rescue and Arconis True Image. These two applications are very similar which makes the difference only in appearance and in terms of ease of use.